2022
DOI: 10.21203/rs.3.rs-1892847/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Presence of Orthorexia Nervosa in Individuals With Type 2 Diabetes and Its Relationship With Diabetes Self-management

Abstract: Purpose This study was conducted to investigate the relationship between the presence of orthorexia nervosa and diabetes self-management in individuals with type 2 diabetes. Methods The study included 373 individuals with type 2 diabetes between the ages of 18–65 who applied to Akdeniz University Hospital Endocrinology and Metabolic Diseases Polyclinic between January 2022 and May 2022. In the study, a questionnaire including sociodemographic data, information about diabetes, nutritional habits, ORTO-R and "… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Other cross-cultural studies did not show any association between ON tendencies and gender (Brytek-Matera et al, 2020; Obeid et al, 2022). Education level has been inconsistently linked to orthorexia, such that one study found that a higher level of education was associated with higher risk of orthorexia (Douma et al, 2021), while two other studies reported that having a university education decreased the risk of displaying orthorexia tendencies (Altun et al, 2022; Bulut and Yigitbas, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Other cross-cultural studies did not show any association between ON tendencies and gender (Brytek-Matera et al, 2020; Obeid et al, 2022). Education level has been inconsistently linked to orthorexia, such that one study found that a higher level of education was associated with higher risk of orthorexia (Douma et al, 2021), while two other studies reported that having a university education decreased the risk of displaying orthorexia tendencies (Altun et al, 2022; Bulut and Yigitbas, 2022).…”
Section: Introductionmentioning
confidence: 99%